2013
DOI: 10.1007/s10620-013-2768-9
|View full text |Cite
|
Sign up to set email alerts
|

Enemas with n-Acetylcysteine Can Reduce the Level of Oxidative Damage in Cells of the Colonic Mucosa Diverted from the Faecal Stream

Abstract: Intrarectal application of NAC reduces the inflammation as well as DNA oxidative damage and could be beneficial as a complementary agent in the treatment of DC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 38 publications
3
22
0
7
Order By: Relevance
“…ROS are produced in excess by colonic mucosa without intestinal transit. The increased production of superoxide radicals, hydroxyl and hypochlorous acid, which cause oxidative stress, can damage the various defense systems of the colonic mucosa 39 . The damage to these defense systems enables the migration of antigens and bacteria in the intestinal lumen to the intima of sterile layers of the colon wall, thus triggering the inflammatory process found in DC 5,6,9 .…”
Section: (5) 2015 -335mentioning
confidence: 99%
“…ROS are produced in excess by colonic mucosa without intestinal transit. The increased production of superoxide radicals, hydroxyl and hypochlorous acid, which cause oxidative stress, can damage the various defense systems of the colonic mucosa 39 . The damage to these defense systems enables the migration of antigens and bacteria in the intestinal lumen to the intima of sterile layers of the colon wall, thus triggering the inflammatory process found in DC 5,6,9 .…”
Section: (5) 2015 -335mentioning
confidence: 99%
“…19 MDA is a secondary product of lipid oxidation and is considered a potential candidate for being a general biomarker of oxidative stress. As to the quantification of tissue levels of MDA, 1 g of each fragment was placed in 5 mL of phosphate buffer and homogenized by vortex and ultrasound sonication for 30 s, alternately, repeating the process for three times.…”
Section: Determination Of Malondialdehyde (Mda) Levelsmentioning
confidence: 99%
“…Studies have shown that the application of enemas containing substances with antioxidant activity in colonic segments devoid from the fecal stream can protect and preserve the colonic epithelial barrier integrity 12,13,32 . zThese substances can reduce the epithelial damage, improve the inflammation and increase the mucous layer that recovers the colonic mucosa devoid of the fecal stream [1][2][3] .…”
mentioning
confidence: 99%